Organizational and Professional Characteristics Predicting External Communications in Canadian Public Health Units - Richard, Lucie (Can J Public Health, 2001)
This study is a survey of administrative divisions involved in tobacco programs in Canadian public health units. It aims to identify correlates of public health units’ contacts and collaborations with external agencies, as predisposing factors in their capacity to innovate. Heads of 124 divisions involved in tobacco control completed a questionnaire about their budgets, staff, and management practices. In each of these divisions, professionals involved in tobacco programs also completed a questionnaire about their characteristics and experience. Results showed a high level of contacts and collaborations with external agencies. Four variables emerged as correlates of external communications: professionals’ degree of access to public health information sources, the diversity of disciplines within the administrative division, the decentralization of authority, and the level of professionals’ participation in decision-making. Because of the potential relationship between innovation and external communication, public health units should consider fostering external communication by management practices and policies, such as favouring professional diversity, increasing access to sources of information, and adopting more decentralized, participatory management.